Detrital and volcanic zircon U–Pb ages from southern Mendoza (Argentina): An insight on the source regions in the northern part of the Neuquén Basin. (December 2015) - Naipauer, Maximiliano; Tapia, Felipe; Mescua, José; Farías, Marcelo; Pimentel, Marcio M.; Ramos, Victor A.
Abstract: The infill of the Neuquén Basin recorded the Meso-Cenozoic geological and tectonic evolution of the southern Central Andes being an excellent site to investigate how the pattern of detrital zircon ages varies trough time. In this work we analyze the U–Pb (LA–MC–ICP–MS) zircon ages from sedimentary and volcanic rocks related to synrift and retroarc stages of the northern part of the Neuquén Basin. These data define the crystallization age of the synrift volcanism at 223 ± 2 Ma (Cerro Negro Andesite) and the maximum depositional age of the original synrift sediments at ca. 204 Ma (El Freno Formation). Two different pulses of rifting could be recognized according to the absolute ages, the oldest developed during the Norian and the younger during the Rhaetian–Sinemurian. The source regions of the El Freno Formation show that the Choiyoi magmatic province was the main source rock of sediment supply. An important amount of detrital zircons with Triassic ages was identified and interpreted as a source area related to the synrift magmatism. The maximum depositional age calculated for the Tordillo Formation in the Atuel-La Valenciana depocenter is at ca. 149 Ma; as well as in other places of the Neuquén Basin, the U–Pb ages calculated in the Late Jurassic Tordillo Formation do not agree with the absolute age of the Kimmeridgian–Tithonian boundary (ca. 152 Ma). The main source region of sediment in the Tordillo Formation was the Andean magmatic arc. Basement regions were also present with age peaks at the Carboniferous, Neoproterozoic, and Mesoproterozoic; these regions were probably located to the east in the San Rafael Block. The pattern of zircon ages summarized for the Late Jurassic Tordillo and Lagunillas formations were interpreted as a record of the magmatic activity during the Triassic and Jurassic in the southern Central Andes. A waning of the magmatism is inferred to have happened during the Triassic. The evident lack of ages observed around ca. 200 Ma suggests cessation of the synrift magmatism. The later increase in magmatic activity during the Early Jurassic is attributed to the onset of Andean subduction, with maximum peaks at ca. 191 and 179 Ma. The trough at ca. 165 Ma and the later increase in the Late Jurassic could be explained by changes in the relative convergence rate in the Andean subduction regime, or by the shift to a more mafic composition of the magmatism with minor zircon fertility. Graphical abstract: Highlights: Two pulses of rifting could be recognized, the oldest has a Norian age and the younger a Rhaetian–Sinemurian age. The maximum depositional age for the Tordillo Formation in the Atuel-La Valenciana depocenter is at ca. 149 Ma. The main source region in the Tordillo Formation was the Andean magmatic arc, but basement rocks were also present. The zircon ages summarized for the Late Jurassic sediments were interpreted as a record of the Andean magmatic activity.